2012
DOI: 10.1371/journal.pone.0048370
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid IL-12p40, CXCL13 and IL-8 as a Combinatorial Biomarker of Active Intrathecal Inflammation

Abstract: Diagnosis and management of the neuroinflammatory diseases of the central nervous system (CNS) are hindered by the lack of reliable biomarkers of active intrathecal inflammation. We hypothesized that measuring several putative inflammatory biomarkers simultaneously will augment specificity and sensitivity of the biomarker to the clinically useful range. Based on our pilot experiment in which we measured 18 inflammatory biomarkers in 10-fold concentrated cerebrospinal fluid (CSF) derived from 16 untreated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 60 publications
10
58
1
Order By: Relevance
“…12 IL-8 is produced intrathecally by a wide array of cell types, regulating recruitment of monocytes and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 IL-8 is produced intrathecally by a wide array of cell types, regulating recruitment of monocytes and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…9 Importantly, elevated cerebrospinal fluid (CSF) IL-8 levels have been observed in infective and noninfective neuroinflammatory conditions, 10,11 and have been described as sensitive biomarker of central active inflammation. 12 In MS, IL-8 receptor was detected on oligodendrocytes around active and silent lesions, and hypertrophic astrocytes stain strongly for IL-8 in active MS lesions. 13 On this basis, we postulated that CSF IL-8 could be used as a valid biomarker of subclinical intrathecal inflammation, and as a sensitive predictor of disease activity in prodromal and early MS.…”
Section: Introductionmentioning
confidence: 92%
“…Although some reports observed increased CSF IL-8 concentrations within patients with bacterial meningitis (12,21,43,(49)(50)(51), others demonstrated that IL-8 tends to be higher within aseptic meningitis cohorts (51). Regardless, IL-8 is thought to be a potent marker of oxidative stress that enables neutrophilic migration to areas of insult (49,52). Therefore, in our study, it is postulated that raised IL-8 levels may be related to the clinical presentation of meningitis in general, regardless of its etiology.…”
Section: Discussionmentioning
confidence: 99%
“…While our dynamic observations suggest pathogenic role of activated members of myeloid lineage (e.g., macrophages, microglia, and myeloid DCs) in axonal damage associated with MS, correlation cannot prove causation. Indeed, activation of myeloid lineage may also be secondary to danger‐associated molecular patterns released upon demyelination 26. This interpretation is supported by the fact that we observed only trend, which did not reach statistical significance, for systemic (i.e., serum) inhibition of CHIT3L1 levels upon initiation of daclizumab therapy, with no significant correlations between two compartments (data not shown).…”
Section: Discussionmentioning
confidence: 50%